THE “GOLDEN AGE” OF THE ITALIAN LITERATURE AND PHILOSOPHICAL THINKING - Lakhtionova, Kateryna (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The article is devoted to the study of the development and the heyday of Italian literature and philosophy in the period of so-called “Golden Ages” of the Renaissance, 15th-16th centuries. The main principles for the appearance of the new philosophical currents, so-called new natural philosophy and Italian averroism (a transformation of ideas of Muhammad Ibn Rushd (Averroè)) and the actual philosophical principles are given. The basis for the origin of typography art in Middle Age Italy, the activity of glorious Italian writers and the decay of the “Golden Age” is presented. Interesting data about the functioning of typographies in Italy, proven by the British Museum of Typography, is provided.___________References:• Bassé, Collectio in unum corpus omnium librorum (Frankfurt am Main, 1592), 334.• Birkenmajer, Études d’histoire des sciences et de la philosophie du moyen âge (Wroclaw, 1970), 698.• Enciclopedia Zanichelli a cura di Edigeo, Dizionario enciclopedico di Arti, Scienza, Tecnicha, Lettera, Filosofia, Storia, Geografia, Diritto, Economia (Bologna, 1997), 2048.
Keywords: The “Golden Age”, Plato's philosophy, modus vivendi of the Middle Ages, averroism, new natural philosophy